Success Factors and Strategic Planning: Rebuilding an Academic Library Digitization Program - Lampert, Cory; Vaughan, Jason (Information Technology and Libraries, 2009)
This paper discusses a dual approach of case study and research survey to investigate the complex factors in sustaining academic library digitization programs. The case study involves the background of the University of Nevada, Las Vegas (UNLV) Libraries’ digitization program and elaborates on the authors’ efforts to gain staff support for this program. A related survey was administered to all Association of Research Libraries (ARL) members, seeking to collect baseline data on their digital collections, understand their respective administrative frameworks, and to gather feedback on both negative obstacles and positive inputs affecting their success. Results from the survey, combined with the authors’ local experience, point to several potential success factors including staff skill sets, funding, and strategic planning.